(untitled) (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
The purpose of this research is to examine how the existence and participation of the community in maintaining the Syawalan Tradition in Bungo Village, Wedung Subdistrict, Demak Regency, especially in the present era. This research was conducted using a qualitative research type with a descriptive qualitative approach. The implementation of this research was carried out using several methods such as field observations, interviews with local traditional leaders and documentation. The final results of the study indicate that the existence of the Syawalan Tradition in Bungo Village, Wedung Subdistrict, Demak Regency is still preserved until now. Evidence of Syawalan’s existence can be seen from the public interest and participation in the implementation of the Syawalan Tradition. The community’s participation in maintaining the Syawalan tradition is proven by the people who are full of enthusiasm and volunteer to bring their marine products in an effort to preserve this tradition passed down from generation to generation. One of them is by continuing to routinely carry out the Syawalan tradition and further develop it into the tourism and economy sectors without losing the identity and philosophy of the Syawalan tradition. The process of explaining the ’Gorampe’ into the sea became an interesting session because it was the highlight of the Syawalan Tradition.